Coping Strategies and Religiosity as Predictors of Mental Well-Being among Arab Teachers in Israel - Egbaria, Hamza (European Scientific Journal, ESJ, 2026)
This study examined whether coping strategies and religiosity predict mental well-being among Arab teachers in Israel. Participants were 415 Arab teachers who completed an anonymous online survey including the Warwick–Edinburgh Mental Well-Being Scale, the Brief-COPE, and the Arab Scale for Religiosity. Descriptive findings showed moderate to high levels of problem-focused and emotion-focused coping, lower levels of avoidant coping, and generally high levels of mental well-being and religiosity. Correlation analyses indicated small positive associations between mental well-being and both problem-focused and emotion-focused coping, whereas religiosity showed the strongest positive association with mental well-being. Multiple regression analysis revealed a significant overall model explaining 9.1% of the variance in mental well-being. Religiosity emerged as the strongest unique predictor, while coping styles and demographic variables showed relatively small effects. The findings suggest that religiosity may serve as an important protective resource for teachers’ mental well-being, whereas coping contributes in expected but more modest ways. The study highlights the value of culturally responsive approaches to supporting teacher well-being in the Arab educational context in Israel.